Comparative findings in childhood‐onset versus adult‐onset optic disc pit maculopathy. (2nd May 2012) - Rii, Tosho; Hirakata, Akito; Inoue, Makoto
Abstract: Purpose: To compare the clinical characteristics of eyes with childhood‐onset to those with adult‐onset optic disc pit maculopathy. Methods: Twenty‐seven eyes of 25 patients with optic disc pit maculopathy were reviewed. The clinical characteristics, clinical history including a history of blunt trauma, ophthalmoscopic evaluations and intraoperative findings in the childhood‐onset (age <15 years, four eyes of four patients) cases were compared with those in the adult‐onset (≥15 years, 23 eyes of 21 patients) cases of optic disc pit maculopathy. The strength of the vitreous adhesions was graded by what was required to create a posterior vitreous detachment (PVD); grade 1 = with vitreous cutter, grade 2 = by microhook or forceps and grade 3 = by forceps with removal of remnants of Cloquet's canal. Results: The incidence of visual impairments following blunt trauma was significantly higher in childhood‐onset (three of four eyes) than that of adult‐onset (0 of 23 eyes, p = 0.0014). Vitreous surgery with creation of a PVD was performed in the four childhood‐onset eyes and 18 adult‐onset eyes after an absence of a spontaneous resolution. The grade of the vitreous adhesions was significantly higher in childhood‐onset than in adult‐onset eyes (p = 0.0096). Conclusions: An ocular trauma may provide an opportunity to detect optic disc pits. However, childhood‐onset optic disc pit maculopathy was noted most commonly following blunt ocular trauma in eyes with a strong vitreous adhesion to the optic disc margin.